(untitled) (International Journal of Technology and Management Research, 2021)
This is a study showcasing the utilization and knowledge of Counselling Services by Graduate Students at KNUST. The counselling Center of KNUST has been in existence over a decade and most of the clients that patronize its services are undergraduate students with few being Graduate Students. This paper was basically aimed at examining the level of awareness the KNUST Counselling Center, the services provided for members of the university community including graduate students and patronage of the services among Graduate students. There is minimal literature about studies done on Graduate students and counselling and there has not been such study to examine the impact of counselling among Graduate students in a university in Ghana. Therefore, it is hoped that this study will lead to further studies among graduate students towards better ways of resolving their issues to improve their mental health. From the study, most Graduate students attest to the fact that Counselling is very important and some confirmed that they would recommend the KNUST-Counselling Center to other students. The services and benefits of the KNUST Counselling Center are described in this paper. Alternative ways for effective utilization of the services of the counselling center are explained to support graduate students to improve their mental heal while in school. Citation:De-Graft Adjei, V., Nuako, R. and Peasah, B. O. S. (2021). Relevance of Counselling Services among Graduate Students at Kwame Nkrumah University of Science and Technology, (KNUST), Kumasi, Ghana. International Journal of Technology and Management Research (IJTMR), Vol. 6 (2): Pp.81-86. Received: April 19, 2020 Accepted: September 1, 2021